2021
DOI: 10.31234/osf.io/tdbnh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online measures of looking and learning in infancy

Abstract: Infants in laboratory settings look longer at impossible than possible events, learn better about objects that behave surprisingly, and match people’s utterances to the objects that likely elicited them. The paradigms that reveal these behaviors have become cornerstones of research on preverbal cognition. But less is known about whether these canonical behaviors generalize in naturalistic environments. Here we describe a series of online protocols that replicate classic laboratory findings, detailing our metho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 2 publications
(2 reference statements)
1
18
0
Order By: Relevance
“…In addition to these platforms, developmental researchers have been using Zoom for experimenter-mediated studies. For example, Smith-Flores et al (2021) used Zoom to replicate several in-lab findings using violation of expectation paradigms with 15-month-old. Importantly, Smith-Flores et al (2021) reported global measures of looking-time (i.e., average proportion of looks), but did not examine moment-by-moment changes in visual attention in response to a stimulus, as is common with lab-based experiments focused on early language development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these platforms, developmental researchers have been using Zoom for experimenter-mediated studies. For example, Smith-Flores et al (2021) used Zoom to replicate several in-lab findings using violation of expectation paradigms with 15-month-old. Importantly, Smith-Flores et al (2021) reported global measures of looking-time (i.e., average proportion of looks), but did not examine moment-by-moment changes in visual attention in response to a stimulus, as is common with lab-based experiments focused on early language development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Smith-Flores et al (2021) used Zoom to replicate several in-lab findings using violation of expectation paradigms with 15-month-old. Importantly, Smith-Flores et al (2021) reported global measures of looking-time (i.e., average proportion of looks), but did not examine moment-by-moment changes in visual attention in response to a stimulus, as is common with lab-based experiments focused on early language development. Although Sheskin and Keil (2018) and Smith-Flores et al (2021) suggest that experimenter-moderated data collection is promising, it is unclear how variability between participants' home set-ups impacts the subsequent data quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible factor that may have limited infants' success in the present online experiments is the stimuli's presentation on small, personal computer screens. For example, while Smith-Flores et al (2021) found looking-time results with toddlers tested online that were largely consistent with lab-based results, they speculated that their one null-finding -that infants failed to look longer at events in which an object appeared to move through another object after rolling down a ramp -may have been due to the events' being presented on a small screen, which minimized the visibility and salience of the violating object's trajectory. Similarly, the small screens used in the present study may have limited the visual saliency of the subtle shape changes.…”
Section: Discussionmentioning
confidence: 74%
“…Several recent online studies have found results that are mostly consistent with in-lab results using either the moderated video-chat or unmoderated approach. These studies have nevertheless adapted forced-choice paradigms with children or looking-time paradigms with older infants and toddlers like preferential or "violation-of-expectation" paradigms (Leshin, RUNNING HEAD: BRINGING HOME BABY EUCLID 4 Leslie, & Rhodes, 2020;Lo et al, 2021;Nussenbaum, Scheuplein, Phaneuf, Evans, & Hartley, 2020;Sheskin & Keil, 2018;Smith-Flores, Perez, Zhang, & Feigenson, 2021).…”
Section: Introductionmentioning
confidence: 99%